Upaya Purchasing Dalam Menghadapi Permasalahan Pengadaan Barang Di Crystal Lotus Hotel Yogyakarta - Mayasari, Citra Unik; Nurjanah, Siti (JURNAL PENDIDIKAN DAN KELUARGA, 2020)
Purchasing is part of the accounting department whose job is as a buyer as well as procurement of goods in the form of services and materials and providers of hotel needs that are ordered to vendors. The problem that often occurs in the procurement of goods is that there is often no availability of goods to vendors when there is a request from the hotel. The research method used is qualitative descriptive and data collection techniques used are observation, interviews, documentation, and literature study. The results of this study are in the form of constraints that often occur in crystal lotus Yogyakarta hotels, namely late delivery of goods, goods that do not match the type and quantity ordered, lack of quality and quantity safeguards and frequent increases in the price of goods, these constraints adversely affect operations hotels, such as guest complaints and hotel cost overruns. The solution to deal with the obstacles experienced by purchasing is that the purchasing party is strived to find a replacement for a vendor that is better and can be consistent with the contract system that has been established and has been agreed by both parties. Keywords: Purchasing, Vendors, Procurement of goods